(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Automation of laboratory testing has become a key area of development in modern medicine. This article analyzes the main advantages of automation, such as increased accuracy, reduced time consumption, and minimization of human error. It also discusses the challenges associated with implementing automated systems, including staff training, high initial costs, and standardization issues.